2014
DOI: 10.3109/02770903.2013.879880
|View full text |Cite
|
Sign up to set email alerts
|

Associations of maternal asthma severity and control with pregnancy complications

Abstract: The risk of gestational diabetes was not associated with asthma severity or control, and the risk of PIH was not associated with asthma severity. However, further studies are needed to clarify the association between asthma control and PIH. The increased risk of cesarean among women with severe asthma may be explained by the physician's and patient's concerns over the safety of normal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…19 Interestingly, a more recent meta-analysis conducted by the same study group indicated that maternal asthma was consistently associated with an increased risk of low birth weight and preeclampsia, whereas the risks of preterm delivery and preterm labor were reduced to nonsignificant levels by active asthma management with the potential to reduce exacerbations. 10 In addition, more increased risk of pregnancy-induced hypertension among uncontrolled asthma was reported by Blais et al 37 The rate of cesarean section in our study subjects with asthma was 19.4% (27.1% in group A and 18.9% in group B), which was not higher than the average cesarean delivery rate of around 36% of all births in Korea between 2011 and 2013. However, patients who had acute exacerbations during pregnancy were more likely to undergo cesarean section than those who had not, and the significance was maintained, even after excluding certain indications for elective cesarean section or failed induction.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…19 Interestingly, a more recent meta-analysis conducted by the same study group indicated that maternal asthma was consistently associated with an increased risk of low birth weight and preeclampsia, whereas the risks of preterm delivery and preterm labor were reduced to nonsignificant levels by active asthma management with the potential to reduce exacerbations. 10 In addition, more increased risk of pregnancy-induced hypertension among uncontrolled asthma was reported by Blais et al 37 The rate of cesarean section in our study subjects with asthma was 19.4% (27.1% in group A and 18.9% in group B), which was not higher than the average cesarean delivery rate of around 36% of all births in Korea between 2011 and 2013. However, patients who had acute exacerbations during pregnancy were more likely to undergo cesarean section than those who had not, and the significance was maintained, even after excluding certain indications for elective cesarean section or failed induction.…”
Section: Discussionmentioning
confidence: 47%
“…Each pregnant case was matched to 15 nonpregnant female control subjects based on 2 factors: the presence or absence of asthma exacerbation within 1 year before the analysis period and age by decade (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and 40-49 years). The matching ratio was chosen as 15:1 because it was the lowest ratio of control subjects to pregnant cases among the matched pairs in accordance with the presence of asthma exacerbation in each age decade (see Table E2 in this article's Online Repository at www.jacionline.org).…”
Section: Discussionmentioning
confidence: 99%
“…Assessing asthma severity 18 studies used 20 different algorithms to assess asthma severity (supplementary table E10) as binary (i.e. severe versus nonsevere asthma) [15,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] or ordinal variables (mild, moderate and severe asthma [39]; low-, moderate-and high-risk asthma [40]). The algorithms were based on one or more of the following asthma-related variables: number and/or dosage of prescriptions (i.e.…”
Section: Defining Asthmamentioning
confidence: 99%
“…Defining exacerbations 24 studies defined exacerbations using EHR-derived data (supplementary table E11) as a dichotomous variable (absent versus present) [16, 17, 23, 27, 30-32, 35, 37-39, 42-44, 46-54] or stratified into absent, moderate and severe [55]. OCS prescriptions were used as a marker for exacerbations in 17 studies, either alone [23,30,31,35,39,42,47,48,53] or with a concurrent asthma encounter (e.g. a general practice, outpatient or emergency department visit, or hospitalisation within 5 or 7 days) [16,17,32,37,38,46,52,54].…”
Section: Assessing Asthma Controlmentioning
confidence: 99%
See 1 more Smart Citation